2007
DOI: 10.1590/s0100-879x2006005000156
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents inflammation and oxidative stress caused by abdominopelvic and total body irradiation of rat small intestine

Abstract: We investigated the day-night differences in intestinal oxidativeinjury and the inflammatory response following total body (TB) or abdominopelvic (AP) irradiation, and the influence of melatonin administration on tissue injury induced by radiation. Rats (male Wistar, weighing 220-280 g) in the irradiated groups were exposed to a dose of 8 Gy to the TB or AP region in the morning (resting period -1 h after light onset) or evening (activity span -13 h after light onset). Vehicle or melatonin was administered imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
18
0
2
Order By: Relevance
“…Radiotherapy (RT) has an important place in the treatment of abdominopelvic cancers (1). The most important reason for limiting the RT dosage is that, during RT, normal tissues are exposed to radiation along with the cancerous tissues (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy (RT) has an important place in the treatment of abdominopelvic cancers (1). The most important reason for limiting the RT dosage is that, during RT, normal tissues are exposed to radiation along with the cancerous tissues (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, chemical agents and oral nutritional supplements were used to reduce these complications associated with RT (1,3,7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Kronobiyolojinin, bu konuyu araştıran alt bilim dalı kronotoksisite olarak adlandırılmaktadır. Radyoterapinin, sıçanlarda uygulanma zamanına bağlı olarak farklı etkiler oluştura-bileceği daha önceki araştırmalarımız sonucunda sunulmuştur [16][17][18] . Literatürde de, 12 saatlik aydınlık-karanlık döngüsünde bırakılan fare ve sıçanlarda, tüm vücuda uygulanan iyonize radyasyonun kronobiyolojik etkisi detaylı olarak derlenmiştir 25,26 .…”
Section: Tartişma Ve Sonuçunclassified
“…Güçlü antioksidan özelliğinin yanı sıra melatoninin radioprotektif (ışıma-koruyucu) etkisi olduğu da bilinmektedir. Daha önce sıçan ince bağırsağında, akciğe-rinde ve testisinde yapmış olduğumuz çalışmalarda iyonize radyasyonun ve melatoninin etkileri araştırılmıştır [16][17][18][19] . Literatürde radyasyonun pineal bez üzerine ince yapı düze-yinde neden olabileceği zedelenme ya da pineal bezden üretilen melatonin miktarındaki değişimler kısmen araştırıl-mış olmakla birlikte 15,20 , radyasyonun oluşturduğu zedelenmenin ve ekzojen uygulanan melatoninin bu zedelenme üzerindeki etkisinin araştırıldığı çalışmalar henüz netlik kazanmamıştır.…”
Section: Introductionunclassified
“…Following radiotherapy, the risk of normal tissue complication constitutes a significant clinical concern and limits the radiation dose that can be delivered to the patients [2]. Oxidative damage is considered to be one of the most popular and important effects of radiotherapy in the liver that induces generation of reactive oxygen species (ROS), which are per se inducers of apoptosis, and radiotherapy seems to be able to induce an apoptotic program through ROS generation [3]. Gene expression studies have revealed the existence of more than one pathway regulating growth inhibition and apoptotic processes [4].…”
Section: Introductionmentioning
confidence: 99%